Testes de cointegração da paridade do poder de compra para a economia brasileira: 1870-1906 - Menezes, Flávio M.; Resende, Marcelo (Estudos Econômicos (São Paulo), 1996)
This paper aims at empirically testing the validity of the purchasing power parity (PPP) hypothesis for the Brazilian economy along the period 1870-1906; at that period, the economy could be characterisad by a flexible exchange rate regime and by the relative importance of the tradeable goods sector. However, the integration tests for small samples do not support the validity of the PPP hypothesis.